2021
DOI: 10.3390/molecules26113309
|View full text |Cite
|
Sign up to set email alerts
|

Organoboron Compounds: Effective Antibacterial and Antiparasitic Agents

Abstract: The unique electron deficiency and coordination property of boron led to a wide range of applications in chemistry, energy research, materials science and the life sciences. The use of boron-containing compounds as pharmaceutical agents has a long history, and recent developments have produced encouraging strides. Boron agents have been used for both radiotherapy and chemotherapy. In radiotherapy, boron neutron capture therapy (BNCT) has been investigated to treat various types of tumors, such as glioblastoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 109 publications
0
29
0
Order By: Relevance
“…The other cycloaddition partner, acetylenic intermediate 4, was generated by O-alkylation of 2-bromo-3-hydroxybenzaldehyde 3 with propargyl bromide (1.5 equiv.) and Clinically approved quinoline (red) and 1,2,3-triazole (blue) containing drugs (some structures of quinolone-and triazole-based hybrids reported in the literature (a-f) [9][10][11][12][13][14]); and the structure of the compound (cyan, 5) reported in this paper. Square: synthesis of 1,2,3-triazoles using click chemistry.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The other cycloaddition partner, acetylenic intermediate 4, was generated by O-alkylation of 2-bromo-3-hydroxybenzaldehyde 3 with propargyl bromide (1.5 equiv.) and Clinically approved quinoline (red) and 1,2,3-triazole (blue) containing drugs (some structures of quinolone-and triazole-based hybrids reported in the literature (a-f) [9][10][11][12][13][14]); and the structure of the compound (cyan, 5) reported in this paper. Square: synthesis of 1,2,3-triazoles using click chemistry.…”
Section: Resultsmentioning
confidence: 90%
“…Figure 1. Clinically approved quinoline (red) and 1,2,3-triazole (blue) containing drugs (some structures of quinolone-and triazole-based hybrids reported in the literature (a-g) [9][10][11][12][13][14]); and the structure of the compound (cyan, 5) reported in this paper. Square: synthesis of 1,2,3-triazoles using click chemistry.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…These bacteria need B for the biosynthesis of AI-2B, and the MoA that we proposed for NOB complexes could explain why these complexes ensure absorption of neutrons and gamma-radiation when they reach the colon [ 138 , 168 , 169 ]. Additionally, in areas where the natural radiation of the soil is increased, the concentration of B in the blood of animals and humans is very low because B in the body is consumed by natural radiation from the environment and transformed into lithium and helium, but only the 10 B isotope conducts the reaction [ 174 , 175 , 176 ]. In these areas, people have very advanced OA (over 70%) [ 177 , 178 , 179 , 180 ].…”
Section: Discussionmentioning
confidence: 99%
“… Benzoxaboroles, cyclic hemiesters of phenylboronic acids, have been known since 1957 [ 8 ] and received moderate interest until it was found that these compounds bind sugars at a physiological pH [ 9 ]. This allowed not only development of a group of receptors of new type but also for the application of these compounds as biologically active substances with antibacterial, antiprotozoal and antifungal activity [ 10 , 11 , 12 ]. The most famous representative of benzoxaboroles contains a fluorine atom and is used as powerful drug against onychomycosis—Kerydin (Tavaborole) [ 13 ] ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%